Gerakan Ibu Hamil Cerdas Mengonsumsi Obat (GICMO): Upaya Pencegahan Risiko Terkait Penggunaan Obat Selama Kehamilan - Hajar Hajar; Hasnia Hasnia; Nunung Erviany; Sry Wahyuni; Ummul Khair; Indah Sari Purna Lumeno; Nurul Faizin; Reli Sipata; Rini Angraini (Lembaga Pengembangan Kinerja Dosen, 2025)
Medication use during pregnancy is a sensitive issue due to potential risks to both maternal and fetal health. Lack of knowledge among pregnant women about safe medication practices often leads to self-medication errors. The Movement of Smart Pregnant Mothers in Medication Use (GICMO) aims to improve pregnant women’s knowledge and awareness regarding rational and safe drug use during pregnancy. The method used was health education through leaflets, interactive discussions, and case simulations. The results showed an increase in pregnant women’s knowledge about drug safety categories and the importance of consulting health professionals before taking any medication, with an average knowledge score improvement of 35%. Based on the evaluation results before and after the activity, there was a 78% increase in participants’ knowledge regarding safe and risky drug categories during pregnancy, as well as an improvement in their awareness to always consult healthcare professionals before taking any medication. This activity demonstrates that structured health education can be an effective strategy to prevent medication-related risks during pregnancy